2011
DOI: 10.1007/s10165-011-0467-y
|View full text |Cite
|
Sign up to set email alerts
|

A trans-ethnic genetic study of rheumatoid arthritis identified FCGR2A as a candidate common risk factor in Japanese and European populations

Abstract: Rheumatoid arthritis (RA) is a common systemic autoimmune disease and its onset and prognosis are controlled by genetic, immunological, and environmental factors. The HLA locus, particularly HLA-DRB1, is its strongest genetic risk determinant across ethnicities. Several other genes, including PTPN22 and PADI4, show modest association with RA. However, they cover only a part of its genetic components and their relative contribution is different between populations. To identify novel genetic determinants, we too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As shown in Table 4, TBX1 played a role in RA pathology through its immunological function. A study by Meziani et al confirmed the association of TBX1 (rs4819522, P -value = 0.0014) with RA in both Japanese and Europeans using a meta-analysis [58]. The identified SNP in the present study (rs1005133, P -value = 4.08 × 10 −08 ) was in a close proximity with the SNP obtained by Meziani et al (28,427 bp).…”
Section: Discussionsupporting
confidence: 87%
“…As shown in Table 4, TBX1 played a role in RA pathology through its immunological function. A study by Meziani et al confirmed the association of TBX1 (rs4819522, P -value = 0.0014) with RA in both Japanese and Europeans using a meta-analysis [58]. The identified SNP in the present study (rs1005133, P -value = 4.08 × 10 −08 ) was in a close proximity with the SNP obtained by Meziani et al (28,427 bp).…”
Section: Discussionsupporting
confidence: 87%
“…Principal components analysis was also used to assess for population substructure for the Toronto cohort. After removal of SNPs in regions with extensive linkage disequilibrium on chromosomes 5 (44-51.5 Mb), 6 (25-33.5 Mb), 8 (8-12 Mb), 11 (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), and 17 (40)(41)(42)(43), all remaining SNPs on the genome-wide genotyping platform were used to calculate principal components using EigenStrat. Six cases were removed as genetic outliers (defined as values Ͼ6 SD from the mean of any of the first 10 principal components).…”
Section: Methodsmentioning
confidence: 99%
“…After application of quality control filters and imputation of SNPs not determined in the Toronto cohort (as detailed below), 168 SNPs associated with autoimmune diseases remained for analysis (for a complete list, see Supplementary Table 1, available on the Arthritis & Rheumatism web site at http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)1529-0131). These included 58 SNPs associated with Crohn's disease (13, 14, 23, 27, 37, 38), 32 associated with type 1 diabetes (15, 16, 39–42), 23 associated with systemic lupus erythematosus (SLE) (17–21, 43–47), 24 associated with RA (22, 36, 48–50), 12 associated with ulcerative colitis (UC) (23–25, 27, 38, 51), 8 associated with psoriasis (26, 52), 15 associated with celiac disease (53–55), 2 associated with MS (56–58), 2 associated with AS (59), and 1 associated with primary biliary cirrhosis (60). Some of these SNPs have been found to be associated with more than 1 of the listed diseases, which is the reason that the numbers of SNPs associated with individual diseases add up to >168.…”
Section: Methodsmentioning
confidence: 99%
“…The IgG Fc receptors, FccRs, are also major contributors to chronic inflammation caused by IgG immune complexes in systemic lupus erythematous (SLE) and related diseases. Genome wide association studies (GWAS) as well as analysis of individual Fc receptor polymorphisms frequently indicates significant disease association in inflammatory bowel disease, rheumatoid arthritis, a number of vasculitides and systemic lupus erythematous (SLE) (Harley et al 2008;Lessard et al 2013;McGovern et al 2010;Meziani et al 2012;Willcocks et al 2008).…”
Section: Introductionmentioning
confidence: 99%